2002
DOI: 10.1002/humu.10112
|View full text |Cite
|
Sign up to set email alerts
|

TGGE screening of the entireFBN1coding sequence in 126 individuals with marfan syndrome and related fibrillinopathies

Abstract: Mutations in the gene for fibrillin-1 (FBN1) cause Marfan syndrome (MFS), an autosomal dominant heritable disorder of connective tissue with prominent manifestations in the skeletal, ocular, and cardiovascular system. FBN1 mutations have also been identified in a series of related disorders of connective tissue collectively termed type-1 fibrillinopathies. We have developed temperature-gradient gel electrophoresis (TGGE) assays for all 65 FBN1 exons, screened 126 individuals with MFS, other type-1 fibrillinopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 50 publications
6
35
0
Order By: Relevance
“…Among the published mutations, R62C was associated with isolated ectopia lentis in one 31-year-old man with a de novo mutation but with manifestations of classic MFS in two other unrelated individuals with the identical, recurrent mutation [Katzke et al, 2002]. S115C was found in an individual with ectopia lentis and skeletal involvement but not aortic dilatation [Katzke et al, 2002].…”
Section: Mild Marfan-like Disorders Without Aortic Dissectionmentioning
confidence: 98%
“…Among the published mutations, R62C was associated with isolated ectopia lentis in one 31-year-old man with a de novo mutation but with manifestations of classic MFS in two other unrelated individuals with the identical, recurrent mutation [Katzke et al, 2002]. S115C was found in an individual with ectopia lentis and skeletal involvement but not aortic dilatation [Katzke et al, 2002].…”
Section: Mild Marfan-like Disorders Without Aortic Dissectionmentioning
confidence: 98%
“…More than 600 FBN1 mutations are registered in the UMD-FBN1 database for MFS and its associated disorders (http:// www.umd.be:2030/) . The mutation detection rate of FBN1 in MFS varies among studies, ranging from 9% to 91% (Katzke et al 2002;Loeys et al 2004;Tynan et al 1993). This variability could be explained, in part, by the different techniques used, but the most significant influencing factor is likely to be sample bias.…”
Section: Fbn1 Mutation-related Disordersmentioning
confidence: 99%
“…Cysteine substitutions in the vicinity of C538P on exon 13 (this study) such as C570R on exon 14 (previously 13) [Schrijver et al, 1999], or C587Y on exon 15 (previously 14) [Booms et al, 1997] both result in ectopia lentis with some skeletal and integument features, but no cardiac symptoms. Likewise, more distant substitutions such as C776G [Katzke et al, 2002], or C1782R [Adés et al, 2004] have been also shown to have little cardiac effect.…”
Section: Discussionmentioning
confidence: 99%